2017
DOI: 10.1186/s12879-017-2187-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and syphilis co-infection and associated factors among non-commercial men who have sex with men attending a sexually transmitted disease clinic in Shenzhen, China

Abstract: BackgroundAlthough HIV and syphilis co-infection has been frequently observed in men who have sex with men (MSM), only few studies have focused on it. Different subgroups of MSM might exhibit heterogeneous HIV and syphilis risk profiles, indicating that interventions for HIV and HIV-related co-infections may vary with different subgroups of MSM. However, no previous study has investigated HIV and syphilis co-infection among non-commercial MSM (ncMSM) attending a sexually transmitted disease (STD) clinic. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…The study found HIV in 24.2% (129/533), syphilis in 29.8% (159/533) and both infections in 13.13% (70/533) of the subjects. HIV co-infection was thus present in approximately 44% of patients with syphilis [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found HIV in 24.2% (129/533), syphilis in 29.8% (159/533) and both infections in 13.13% (70/533) of the subjects. HIV co-infection was thus present in approximately 44% of patients with syphilis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Zakażenie HIV stwierdzono u 24,2% (129/533) pacjentów, kiłę u 29,8% (159/533), a oba zakażenia jednocześnie u 13,13% (70/533). Zakażenie HIV współistniało u ok. 44% chorych z kiłą [16].…”
Section: Discussionunclassified
“…These questions were correctly answered as “Yes”, but wrongly answered or unknown as “No” (Cronbach’s α = 0.57). Individuals answering six or more questions correctly were defined as having adequate HIV-related knowledge [39].…”
Section: Methodsmentioning
confidence: 99%
“…Despite high HIV prevalence and frequent condomless sex among MSM in China, [1218] there are limited data on MSM extragenital gonorrhea and chlamydia. [19, 20] Better understanding the burden of rectal and pharyngeal gonorrhea and chlamydia can provide useful information for research and screening pilots.…”
Section: Introductionmentioning
confidence: 99%